Optimizing the Use of School Libraries in Improving Students' Literacy Skills at SDN 1 Citamiang - Aida Latifah; Dede Ipan Gumelar; Dinny Mardiana; Suharyanto H Soro (Global Education Journal, 2025)
This study aims to describe the optimization of the use of school libraries in improving the literacy skills of elementary school students through the implementation of management functions. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation involving principals, teachers, and library managers at SDN 1 Citamiang. The results of the study show that the optimization of the use of school libraries is carried out through the stages of planning, organizing, directing, coordinating, and controlling which refer to Henry Fayol's management theory. Planning is carried out by analyzing students' literacy needs and designing literacy programs in a structured manner, such as 15-minute reading, reading corners, and regular visits to the library. Organizing is carried out through a clear division of duties and responsibilities between school principals, teachers, and library managers. Briefings are given on an ongoing basis to build reading habits and improve students' reading comprehension. The coordination established between school elements allows literacy programs to run more regularly and integrated with classroom learning. Control is carried out through periodic monitoring and evaluation of the implementation of programs and the use of library facilities. Overall, optimizing the use of school libraries has a positive impact on improving the literacy skills of elementary school students, especially in fostering interest in reading, reading comprehension, and independent learning habits.